English-Lithuanian Lexical Pseudo-Equivalents - Stankevičienė, Laimutė (Kalbotyra, 2002)
The paper presents a contrastive description and analysis of English and Lithuanian lexical units identical or similar in form (spelling and/or pronunciation) but having some differences in meaning. The semantic structure of lexical pseudo-equivalents has been investigated in order to establish the level of their systemic equivalence in the two languages. The results of the research show that 26% of the selected word pain do not share any denotative/propositional meaning (absolute lexical pseudo-equivalents). The rest 74% share at least one meaning and have at least one different meaning (partial pseudo-equivalents). Among them, cases when the English word has all the meanings of the Lithuanian word and some of its own (the inclusion of Lithuanian into English) account for 51%, while the reverse (Lithuanian words having developed their own meanings in addition to the shared ones) constitutes only 6%. About 17% represent cases of meaning overlap.The comparison also allows us to make some conclusions about the nature and character of borrowing in the two languages. The Lithuanian lexemes in the word pain are mostly borrowings of either Greek or Latin origin, which are more or less isolated in the lexical system of the Lithuanian language from both formal and semantic point-of-view. This is reflected in their narrow, often specific/terminological meaning. Borrowed words tend to remain isolated and very rarely (6%) develop their own meanings. In English lexemes of the same origin are motivated elements of the system with all the properties typical of the ‘native’ word.